The parameterization of wave‐particle interactions in the Outer Radiation Belt. Issue 9 (8th September 2017) - Watt, Clare E. J.; Rae, I. J.; Murphy, K. R.; Anekallu, C.; Bentley, S. N.; Forsyth, C.
Abstract: We explore the use of mean value empirical wave models in diffusion models of the Outer Radiation Belt. We show that magnetospheric wave power is not normally distributed in time and that geomagnetic activity does not provide a deterministic proxy for the temporal variability of wave activity. Our findings indicate that current diffusion models significantly overestimate the action of wave‐particle interactions due to extremely low frequency and very low frequency waves in the magnetosphere. We suggest that other techniques such as stochastic parameterization will lead to a better characterization of subgrid diffusion physics in the Outer Radiation Belt. Key Points: Radiation belt models capture subgrid physics through the use of diffusion coefficients that require wave observations for their calculation Current empirical wave models do not capture the true temporal variability of magnetospheric waves leading to overestimates of diffusion We suggest that methods such as stochastic parameterization of diffusion are superior; there is no evidence that a deterministic wave model exists